PROTECTION SECOND LAYER MENGGUNAKAN MULTI FACTOR AUTHENTICATOR UNTUK MEMVERFIKASI KEABSAHAN ACCOUNT EMAIL DI DALAM ACTIVE DIRECTORY - Subandi, Kotim; Ahmad, Dinar Munggaran; Sugara, Victor Ilyas; Aryani, Adriana Sari; Hermawan, Hermawan (Universitas Teknokrat Indonesia, 2024)
The problem that often occurs is that many users use unsafe devices to carry out the login process, for example using laptops, mobile phones and other devices in public spaces such as terminals, airport stations, public libraries, cafes and even internet cafes. One of the important steps in the security and authentication process. This verification ensures that the account owner has access to the email address used to register or log in to a service. Multi-Factor Authentication (MFA) is a security method that requires users to provide more than one form of authentication to access a system or application. Research focuses on evaluating the security of MFA, using appropriate metrics (such as authentication success rate, successful attack rate, or discovered vulnerabilities) to assess the effectiveness of MFA. Implementing MFA on email accounts is not only a wise security measure, but also a recommended practice to protect personal information and reduce online security risks